Answer:
y
=
−
1
2
⋅
(
x
+
2
)
2
−
1
Step-by-step explanation:
To convert a quadratic from y = ax2 + bx + c form to vertex form, y = a(x - h)2+ k, you use the process of completing the square. Let's see an example. Convert y = 2x2 - 4x + 5 into vertex form, and state the vertex. Equation in y = ax2 + bx + c form.
Very glad I could help you!1
Answer: A
Step-by-step explanation:
I think it is A because p*(10-2). Can = (p*10)-(p*2)
-8 * -4 = 32
Just multiply both numbers and negatives cancel
i believe it would be 5.25
12-5=7
7*12=84
84/ 16 = 5.25
i hope this helps
Answer:
d = 90°
e = 41°
f = 139°
Step-by-step explanation:
d + 90° = 180° (Angles in linear pair)
-> d = 180° - 90°
-> d = 90°
e = 41° (vertical angles)
f + 41° = 180° (Angles in linear pair)
-> f = 180° - 41°
-> f = 139°